PLAGIARISM DETECTION IN RESEARCH OF LECTURERS AND STUDENTS AT BUDI DARMA UNIVERSITY APPLYING THE TURBO ALGORITHM BOYER MOORE - Alwin Fau; Nelly Astuti Hasibuan (INFOKUM, 2022)
Research conducted by students or lecturers is a form of creativity and also a sense of sharing knowledge and experience with others. Research for a lecturer or lecturer is something that must be done by the lecturer because it is part of the lecturer's duties. Research for students is a step that must be carried out by every student at the time of completing studies in each study program that is being carried out. The form of research produced by students and lecturers is in the form of scientific articles. Scientific articles which are the result of research by lecturers and students will be published in certain journals depending on the researcher. Before the research of lecturers and students is published in a journal, the article needs to be checked first to avoid plagiarism in the research. Budi Darma University always has problems with that checking every article being researched by lecturers and students. This study will discuss how the processes and stages are carried out in checking lecturers and students. This research will produce an application that can be used by Budi Darma University in checking scientific articles. The results of checking plagiarism with the Turbo Boyer algorithm can detect more than 75%